Nutrient Changes with the Growth of Hydroponics Cowpea (Vigna unguiculata) Sprouts - Naik, P.K.; Dhawaskar, B.D.; Fatarpekar, D.D.; Chakurkar, E.B.; Swain, B.K.; Singh, N.P. (Indian Journal of Animal Nutrition, 2018)
Hydroponics cowpea (Vigna unguiculata; DU-3) sprouts were produced daily for a period of 15 days in a hydroponics chamber (greenhouse) equipped with automatic sprayer of tap water. Cowpea with seed rate of 2.54 kg/m2 with replicates of 15 were soaked in tap water individually for 4 h. Then, the seeds were strained and spread in the greenhouse trays. Inside the greenhouse, each replicate was allowed to grow up to 6 days after which it was harvested. The fresh yield (kg/kg seed) of hydroponically sprouted cowpea increased whilethat DM yield decreased (P